Design-based research in the context of transitioning to VET : developing interventions through research-practice collaboration - Brahm, Taiga [Verfasser] (My University, 2017)
"The transition from school to vocational education and training (VET) is becoming more difficult for an increasing number of adolescents. Despite the growing significance of this phase, there is hardly any research regarding interventions targeting students' resilience, especially with regard to their capacity to join the labour market. This paper aims at describing the research process of developing three different interventions in cooperation with a number of practitioners who teach in so-called interim solutions. The goal of the paper is, thus, to illustrate how design-based research (DBR) can be conducted in the context of vocational education. The comprehensive three-cycle development of three interventions with the aim of fostering students' conflict management competence, attribution and self-efficacy will be used as a single case study to illustrate a complex DBR project. Each step in the design-research process will be reflected, resulting in a discussion of the possibilities and obstacles of combining formative and summative evaluation in the DBR process." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; Berufsbildungsforschung; Gestaltungsbasierte Forschung; Fallstudie; Berufseinmündung; Zweite Schwelle; Resilienz; Konfliktmanagement; Forschungskooperation; Theorie-Praxis